Analytical Modeling of LEO Satellite Mutual Visibility under Perturbations - Amin, Mohamed R (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
This present study develops an analytical model for mutual visibility in perturbed Low Earth Orbit (LEO), explicitly accounting for Earth’s oblateness (J2 and J3) and atmospheric drag. The framework extends classical geometric visibility calculations to include long-term perturbation effects, thus enabling rapid and reliable prediction of visibility intervals. A series of numerical simulations were conducted on three LEO satellite configurations and revealed that perturbations have the capacity to shift rise–set times, alter event frequency and duration, and generate new visibility intervals. These effects are of particular significance for satellites operating at lower altitudes and those characterized with moderate semi-major axis differences and large inclination disparities. The results of the study underscore the importance of considering secular and long-period perturbations into the planning of reliable communication relay, the management of constellation, and the scheduling of autonomous mission. Importantly, the closed-form formulation enables fast visibility and rise–set prediction without full numerical orbit propagation, supporting preliminary constellation design, inter-satellite link scheduling, and onboard visibility assessment in large LEO networks.